mtDNA Haplogroup M5 Associated with Risk of Colorectal Cancer in South India Population - B. Prathap Naidu; Pallaval Veera Bramhachari (Iraqi Journal of Science, 2021)
The life on earth is driven by energy, supplied by the tiny organelles of the cell called mitochondria and they are usually stated as the powerhouses of the cell. In population genetics, Mitochondrial DNA (mtDNA) is used extensively to categorize individuals or populations. The mutation sites observed in human mtDNA by comparing with the reference sequence (rCRS) are termed into definite human mtDNA haplogroups. Previous studies showed that mtDNA specific haplogroups and polymorphisms were established to be linked with various human diseases, including cancer in numerous populations. Furthermore, it is also known that several mitochondrial DNA polymorphisms are implicated in enhanced production of Reactive Oxygen Species (ROS) which are known to be an increased risk cause for several cancers, including colorectal cancer in Indian patients. Hence in our study, we made high resolution examination on mtDNA hypervariable region to trace the association of specific mtDNA haplogroup with colorectal cancer in south Indian populations. We report that mtDNA Haplogroup M was observed in 60% of the colorectal cancer patients and around 55% in the studied control samples. Haplogroup M is the most frequent mtDNA cluster found among south Indian populations. We further sub-lineated macro haplogroup M and found sub haplogroups (M8, M7, M6, M5, M3 and M2) in varied frequencies. In particular, we found significant association of haplogroup M5 with colorectal cancer patients (p = 0.026). Haplogroup M5 was observed in 12% of colorectal cancer patients in south Indian patients and in 3.3% of the control populations. These results suggest that individuals with haplogroup M5 may have significant risk to develop colorectal cancer.